Stakeholder Engagement and Training Meeting on Climate Information Services and Climate Smart Agriculture - International Crops Research Institute for the Semi-Arid Tropics (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
A two-day workshop meeting was held on ‘Stakeholder Engagement and Training on Climate Information Services and Climate Smart Agriculture at Jacaranda Hotel, Nairobi from 8th to 9th December 2022. As part of capacity building activities for agricultural value chain actors under the Accelerating the Impact of CGIAR Climate Research for Africa (AICCRA- Kenya) project, the main purpose of the meeting was to strengthen the capacity of various agricultural value chain actors in Kitui, Makueni and Taita Taveta to enhance a climate resilient agricultural system.